PODCAST SEBAGAI MEDIA DAKWAH ALTERNATIF DI ERA PADEMI COVID-19 - MUSLEM, MUSLEM (Universitas Islam Negeri (UIN) Mataram, 2021)
Podcasts are becoming one of the alternative media that are being loved by millennials today, the development of technology makes podcasts more flexible and easier to use. Podcasts focus more on audio so users can listen to them anywhere and anytime. Restrictions on social activities due to Covid-19 make podcasts more and more space in the community. Various advantages that podcast have can make podcasts an alternative medium of da'wah in the era of Covid-19